Stability Modeling of Groyne-Type Structure with Embankment in Pelangai River, Pesisir Selatan Regency, West Sumatra - Zulhendra, Riko; Arif, Maulana; Adi Putra; Dicky Febri Hadi (Journal of Civil Engineering and Planning (JCEP), 2024)
Erosion is one of the exogenic processes that commonly occur around river dynamics. Intensive erosion occurs at the riverbank area, which has the potential to cause the slope on that side to collapse. Therefore, a groyne-type structure is required to prevent this from happening. A groyne-type structure is planned to reduce the impact of erosion in the Pelangai River with embankment. This research aims to determine the stability of the groyne with embankment design using Plaxis 2D software. Plaxis 2D modeling uses soil input parameters based on CPT, SPT, and groyne structure with approximation parameters. The modeling results show that with the addition of groyne, embankment and traffic load, the safety number drops from 1.906 to 1.241. This figure does not meet the safe number limit according to SNI Geotechnical 8460 of 2017, which requires a minimum safe number of 1.25. In addition, the addition of groyne, embankment, and traffic load resulted in soil settlement of up to 6.3 cm, which is still considered safe.